2006
DOI: 10.1128/jvi.00312-06
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Naturally Occurring Recombinant Genotype 2/6 Hepatitis C Virus

Abstract: Hepatitis C viruses (HCVs) display a high level of sequence diversity and are currently classified into six genotypes and an increasing number of subtypes. Most likely, this heterogeneity is caused by genetic drift; evidence for recombination is scarce. To study the molecular heterogeneity of HCV in Vietnam, we analyzed 58 HCV RNA-positive sera from Vietnamese blood donors by sequence analysis of the CORE and NS5B regions. Phylogenetic analyses revealed the presence of genotype 1 (38%), genotype 2 (10.3%), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
99
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(108 citation statements)
references
References 58 publications
6
99
1
2
Order By: Relevance
“…The ED43/JFH1-␤ and -␥ recombinants with junctions inside NS2 and at the NS2/NS3 cleavage site, respectively, were viable. Interestingly, naturally occurring intergenotypic recombinant isolates with the same 3Ј-terminal junctions as used in the ␤-and ␥-but not in the ␣-construct have been described (13,19). A study on JFH1-based inter-and intragenotypic recombinants suggested that the ␣-junction (termed C3), located in the N terminus of NS2, in general was favorable in obtaining the most efficient phenotype (9).…”
Section: Discussionmentioning
confidence: 99%
“…The ED43/JFH1-␤ and -␥ recombinants with junctions inside NS2 and at the NS2/NS3 cleavage site, respectively, were viable. Interestingly, naturally occurring intergenotypic recombinant isolates with the same 3Ј-terminal junctions as used in the ␤-and ␥-but not in the ␣-construct have been described (13,19). A study on JFH1-based inter-and intragenotypic recombinants suggested that the ␣-junction (termed C3), located in the N terminus of NS2, in general was favorable in obtaining the most efficient phenotype (9).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, at least ten other different intergenotypic recombinant forms (RFs) of HCV have been described and are totally or partially characterised (Table 1). Within this group of recombinants, we can observe the presence of recombinant forms between genotypes 2 and 6 described in Vietnam [130] and Taiwan [131] , between genotypes 2 and 5 described in France [132] , between genotypes 3 and 1 in Taiwan [131] and China [133] , and between genotypes 2 and 1 reported in Japan, the United States and the Philippines [134][135][136][137] . It is interesting to note that recombinant forms found so far have a wide geographic distribution.…”
Section: Recombinationmentioning
confidence: 99%
“…Currently, the global spread of HCV has accelerated with the advent of more methods and frequency of transmission routes of populations 21 which probably accounts for the appearance of pattern III HCV. However, we have found three patterns designated as II, IV, and V which may have arisen from mutation by recombination in the local population 22,23 . Mutations of the core region impact on clinical outcomes [24][25][26] .…”
Section: Discussionmentioning
confidence: 99%